Percepciones e intención de vacunar contra el dengue de los padres de hijos de 10 a 16 años de Iquitos, 2025 - Reátegui Yglesias, Estefanía (2025)
Objective: To determine the perceptions and intention to vaccinate against dengue among parents of children aged 10 to 16 years in Iquitos, in 2025. Methods: A quantitative, observational, analytical, cross-sectional, and prospective study was conducted using simple random probabilistic sampling. A survey validated by expert judgment was applied to 191 parents. Results: The intention to vaccinate was high (90.05%), especially among younger parents (U test=341.5; p=0.02), those with technical education (X²=24.224; p=0.011), and residents of Punchana (X²=34.388; p<0.001). It was also higher among those whose children had a complete vaccination schedule (X²=14.68; p=0.048) and who perceived a risk of infection (X²=43.929; p<0.001), severe illness (X²=11.909; p=0.006), or death (X²=9.757; p=0.017). Uncertainty about possible consequences was associated with lower vaccination intention (X²=18.130; p=0.001). Parents who considered the vaccine necessary (X²=146.723; p<0.001), effective (X²=64.898; p<0.001), safe (X²=133.940; p<0.001), or mandatory (X²=133.051; p<0.001), and who trusted healthcare workers' recommendations (X²=89.587; p<0.001), showed greater willingness. In contrast, incomplete communication (X²=80.198; p<0.001) and lack of knowledge about side effects (X²=19.334; p=0.001) reduced intention. Acceptance was linked to the belief that the vaccine does not cause the disease (X²=59.011; p<0.001), is compatible with other vaccines (X²=55.165; p<0.001), and has mild side effects such as headache (X²=13.407; p=0.009), fever (X²=23.127; p<0.001), or redness (X²=10.346; p=0.031), with no serious short-term (X²=60.015; p<0.001) or longterm (X²=110.954; p<0.001) effects. Main motivations included protecting children's health (X²=56.234; p<0.001), boosting immunity (X²=30.059; p<0.001), and preventing epidemics (X²=18.635; p=0.001); while barriers included the novelty of the vaccine (X²=19.625; p=0.001) and negative perceptions of its safety and efficacy (X²=17.880; p=0.001). Conclusion: Despite high vaccination intention in Iquitos, it is necessary to strengthen educational strategies and monitor perceptions to ensure sustained acceptance.